Lithium Enhances Hippocampal Glucose Metabolism in an In Vitro Mice Model of Alzheimer's Disease - Gherardelli, Camila; Cisternas, Pedro; Inestrosa, Nibaldo C. (My University, 2022)
Impaired cerebral glucose metabolism is an early event that contributes to the pathogenesis of Alzheimer's disease (AD). Importantly, restoring glucose availability by pharmacological agents or genetic manipulation has been shown to protect against A beta toxicity, ameliorate AD pathology, and increase lifespan. Lithium, a therapeutic agent widely used as a treatment for mood disorders, has been shown to attenuate AD pathology and promote glucose metabolism in skeletal muscle. However, despite its widespread use in neuropsychiatric disorders, lithium's effects on the brain have been poorly characterized. Here we evaluated the effect of lithium on glucose metabolism in hippocampal neurons from wild-type (WT) and APPSwe/PS1 Delta E9 (APP/PS1) mice. Our results showed that lithium significantly stimulates glucose uptake and replenishes ATP levels by preferential oxidation of glucose through glycolysis in neurons from WT mice. This increase was also accompanied by a strong increase in glucose transporter 3 (Glut3), the major carrier responsible for glucose uptake in neurons. Similarly, using hippocampal slices from APP-PS1 mice, we demonstrate that lithium increases glucose uptake, glycolytic rate, and the ATP:ADP ratio in a process that also involves the activation of AMPK. Together, our findings indicate that lithium stimulates glucose metabolism and can act as a potential therapeutic agent in AD.
Keywords: lithium; glucose; metabolism; alzheimer's disease